2014
DOI: 10.3233/xst-140444
|View full text |Cite
|
Sign up to set email alerts
|

Detection of uric acid depositing in tophaceous gout using a new dual energy spectral CT technology

Abstract: OBJECTIVE: To assess the feasibility and diagnostic value of detecting uric acid depositing among patients with tophaceous gout using a dual energy CT based Gemstone spectral imaging (GSI) technology for qualitative analysis of uric acid. METHODS: Thirty one patients with clinically detectable tophaceous gout and 10 healthy volunteers underwent Discovery CT 750 HD scan with GSI mode. We selected four case groups of tophi, muscles, cortical bone, and cancellous bone. Each has a region of interest (ROI) of 10 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The DECT GSI method has been methodically tested and shown to be able to detect MSU deposits by Li et al 2014 [12]. Kiefer et al compared single source DECT with conventional CT and digital radiography and showed that it had the best diagnostic properties of the three for gout diagnosis [13].…”
Section: Discussionmentioning
confidence: 99%
“…The DECT GSI method has been methodically tested and shown to be able to detect MSU deposits by Li et al 2014 [12]. Kiefer et al compared single source DECT with conventional CT and digital radiography and showed that it had the best diagnostic properties of the three for gout diagnosis [13].…”
Section: Discussionmentioning
confidence: 99%
“…DECT GSI translated two sets of absorption projection data to material density projection data and provided different base material mapping (such as uric acid/calcium pairing, water/iodine pairing, water/calcium pairing, etc.). Base material concentration imaging can better reflect the content of the corresponding components of the tissue, and the uric acid crystal can be visualized more accurately in the uric acid-based map than that in the calcium-based map [19].…”
Section: Dect Examinationmentioning
confidence: 99%
“…Urate‐based material images can detect high urate concentration deposits but cannot detect other types of high concentration crystal deposits. Therefore, spectrum CT‐based material image results and pathology results have good consistency . Dong et al .…”
Section: Diagnosismentioning
confidence: 84%
“…Using the GE Healthcare AW 4.4 workstation and gemstone‐spectral imaging with base material (urate and calcium) mapping, tophi can be detected with urate‐based and calcium‐based images and this clearly shows the bone destruction and condition of tophi adjacent to joints . Li et al .…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation